THE JUDICIAL POWER LIMITATION OF COMMERCIAL COURTS COMPETENCY IN COMMERCIAL DISPUTES - Sobandi, Sobandi (UNISSULA, 2021)
One of the important instruments in a state of law is the existence of an independent judiciary, whether it is based on the doctrine of separation of powers, the notion of a state based on law or democracy. An independent judicial power is not absolute in the sense that it is free to lead to arbitrariness so that there must be restrictions on that power and freedom. The approach method is used a normative juridical approach. The results of the study found that the limitations of judicial power were based on the constitutional basis, namely Article 1 paragraph 3 of the 1945 Constitution, Article 24 of the 1945 Constitution and Article 24 A of the 1945 Constitution. From the concept of separation or division of powers, compose an independent judicial power which is exercised by a Supreme Court and judicial bodies under it and a Constitutional Court. The commercial court as a sub-system within the judicial power is a special court under the general judiciary that has different competencies from other general courts. The implementation of the limitation of judicial power in the competence of the commercial court to realize an independent judicial power is normatively spread out in various laws.